2018
DOI: 10.5194/bg-2018-473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Greenhouse gas and energy fluxes in a boreal peatland forest after clearcutting

Abstract: <p><strong>Abstract.</strong> The most common forest management method in Fennoscandia is rotation forestry including clearcutting and forest regeneration. In clearcutting, stem wood is removed and the logging residues are either removed or left on site. Clearcutting changes the microclimate and vegetation structure at the site, both of which impact the site's carbon balance. Peat soils with poor aeration and high carbon (C) densities are especially prone to such chang… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…These results confirmed that nearly-saturated conditions largely suppressed soil respiration and further caused a large carbon sink. This finding was consistent with the situations in several wet ecosystems, such as tropical peatlands, northern peatlands, and Arctic tundra (Knowles et al 2015;Korkiakoski et al 2019;Hoyt et al 2019). For example, Knowles et al (2015) reported that in a wet tundra ecosystem in the Colorado Rocky Mountains there was a significantly negative relationship between SM and soil respiration when soil moisture was above 0.38; they explained this result through the fact that soil respiration switched from moisture-limited to oxygen diffusion-limited with increasing SM.…”
Section: Impacts Of Shallow Groundwater On Carbon Exchange Of Wet Alpine Meadow Ecosystemsupporting
confidence: 83%
See 1 more Smart Citation
“…These results confirmed that nearly-saturated conditions largely suppressed soil respiration and further caused a large carbon sink. This finding was consistent with the situations in several wet ecosystems, such as tropical peatlands, northern peatlands, and Arctic tundra (Knowles et al 2015;Korkiakoski et al 2019;Hoyt et al 2019). For example, Knowles et al (2015) reported that in a wet tundra ecosystem in the Colorado Rocky Mountains there was a significantly negative relationship between SM and soil respiration when soil moisture was above 0.38; they explained this result through the fact that soil respiration switched from moisture-limited to oxygen diffusion-limited with increasing SM.…”
Section: Impacts Of Shallow Groundwater On Carbon Exchange Of Wet Alpine Meadow Ecosystemsupporting
confidence: 83%
“…These ecosystems generally act as a carbon sink (Kato et al 2006;Li et al 2016;Scholz et al 2018), which however is expected to be reduced and potentially turns into a carbon source in response to future warming, due to the accelerated soil carbon decomposition (Virkkalaet al 2017;Ganjurjav et al 2018;Sun et al2019). Many previous studies reported that climate warming and human activities will change the soil hydrologic conditions and further affecting the soil carbon dynamics of several cold ecosystems, including Arctic tundra, northern peatlands, mires, and bogs (Ise et al2008;Dorrepaal et al 2009;Dinsmore et al 2010;McVeighet al 2014;Schädel et al 2016;Drollinger et al2019;Gockede et al 2019;Korkiakoski et al 2019;Stover & Henry 2019;Swindles et al 2019). However, the mechanisms by which the soil hydrological conditions, such as the shallow groundwater level, affect carbon exchanges in alpine meadow ecosystem are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Forest management in Finland is a strong modifier of ecosystem carbon budgets and usually an unaccounted source of uncertainty in future predictions. The harvesting intensity defines the impact to the ecosystem carbon exchange (Korkiakoski et al, 2018). According to Kalliokoski et al (2018), the future forest productivity was predicted to increase towards the end of the century.…”
Section: Discussionmentioning
confidence: 99%
“…Data for the clear-cut site for two post-treatment years are available through Zenodo (10. 5281/zenodo.3384791, Korkiakoski et al, 2019b). WTL and chlorophyll fluorescence data are made available here.…”
Section: Appendix A: Gap-filling Co 2 Datamentioning
confidence: 99%